Angry Worship and Preaching: Embodying Context and Text in Liturgy – Part 1 - Wepener, Cas (Studia liturgica, 2023)
In a world plagued by injustices such as gender-based violence, racism, poverty, and inequality, preaching and liturgy can foster a prophetic imagination that simultaneously criticizes and energizes. In two articles, the potentially positive role that anger can play in this kind of liturgy and preaching is explored. After a narrative-style introduction, the first article provides a contextual and theoretical background by describing a South African and global context that elicits a wide range of angry responses. It follows with an exploration of anger as an emotion and the importance of the human body, including the emotions and the senses, in the performance of worship and preaching. Furthermore, anger in theological discussions is presented, as well as the practice of listening to anger. Finally, different kinds of anger are described with one specific type, named Lordean rage by Myisha Cherry, being examined as a meaningful type of anger for liturgical praxis. Expressions of Lordean anger as encountered in biblical and present-day contexts can, and even should at times, be embodied in preaching and liturgy. The second article builds on these insights and develops a preliminary liturgical and homiletical praxis theory for angry preaching and worship.